Wide -Awake Local Anesthesia No Tourniquet (WALANT) Procedure for Primary Repair of Traumatic Rupture of Flexor Tendon of the Hand: A Single Center Experience - Kastanis, Grigorios E; P, Kapsetakis; E, Trachanatzi; C, Chaniotakis; M. K., Siligardou; C, Andriopoulos; A, Pantouvaki (International Journal of Innovative Research in Medical Science, 2022)
Reconstruction of flexor tendons of the hand injuries is performed under general or regional anesthesia and tourniquet, in general. During the Covid-19 pandemic period the insufficiency of anesthesiologists created the need to find alternative methods of anesthesia with similar results of the existing ones. Wide awake, local anaesthetic, no-tourniquet technique (WALANT) started to be more popular, and based on the advantages (low cost, no tourniquet, no access of anaesthetic support, intraoperative collaboration to control active motion of flexor tendon reparation) gradually appeared to be a safe technique. Combination of lidocaine and adrenaline allows to ensure local anesthesia and at the same time vasoconstriction. The aim of this study is to estimate the evidence of effectiveness and secure of the WALANT technique in a case series from our hand reconstruction unit according to patient’s satisfaction, complications, and functional outcomes. Material & Method: During the period from April 2021 to September 2022, 34 patients with traumatic lesion of flexor tendon of the hand were treated with tenorrhaphy under WALANT procedure. The flexor tendon zone of traumatic injury was I,II,III, and T1,T2,T3. All patients were operated within 24 hours from the injury and were able to be discharged on the same day. The majority of the operations were performed in a second operative theatre and all performed without anaesthetic support. Results: Overall, Visual Analogue Scores were 0/10, mean rate of patient’s satisfaction was very satisfied in 82.3%, while mean Quick DASH score was 1.38. There were no cases with peri-postoperative complication during the WALANT technique. In all cases there was no need to administrate phentolamine as antidote to adrenaline vasoconstriction or other procedure of anesthesia. Conclusions: WALANT procedure is a safe method in which you can control pain and blood loss from the combination of lidocaine and adrenaline. The absence of tourniquet avoid the intra- postoperative discomfort of the patient, while intraoperative collaboration of the patient offers immediate restoration of active motion of flexor tendon and avoid postoperative complications from tenorrhaphy. Furthermore, patients̓ satisfaction continues to exist high and rate of postoperative complication nonentity.